1962
DOI: 10.3181/00379727-111-27926
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-Cellular Interaction in Tissue Culture.

Abstract: N-methylhydrazine. Their inhibitory action is approximaiely 40 times higher than, e.g., that of L-a-methyldopa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1964
1964
1978
1978

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A great part of the grafted cells are probably quickly being removed by host macrophages. Perhaps estrogen may increase the breakdown of donor cells ( 3 ) and, in addition, impede the division of recipient macrophages (15,16), something which may be relevant to amyloid development (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A great part of the grafted cells are probably quickly being removed by host macrophages. Perhaps estrogen may increase the breakdown of donor cells ( 3 ) and, in addition, impede the division of recipient macrophages (15,16), something which may be relevant to amyloid development (22,23).…”
mentioning
confidence: 99%
“…Blood lymphocytes are, however, only moderately reduced in number and their response to PAH does not point to an inferior function of the lymphocytes in cisrculation. A more important alteration may be a reduced supply of marrow-derived cells to the thymus ( 7 , 14) due to the mitosis-inhibiting effect of estrogen (15,16) and/or the reduced volume of the marrow cavity in estrogen-treated mice (17). The latter possibility is rendered less likely by the observation that there is no correlation between the tendency to skeletal changes and thymoma development in different mouse strains after estrogen treatment ( 18).…”
mentioning
confidence: 99%
“…This is in agreement with the observation that in cultures of with 17-B-estradiol with the GI of the control cultures, it appears that the hormone has caused a depression of the growth rate. Several reports in the past have indicated that estradiol exerts in vitro an inhibitory effect on the growth of various cell types (12)(13)(14)(15)(16). With the exception of an inhibitory effect exerted by estradiol on the incorporation of S '5 in cartilage and aorta of rats (17,18), by and large the estrogens seem to induce an increase in AMPS of the ground substance of various organs (10,(19)(20)(21)(22)(23)(24)(25).…”
Section: A N D C O M M E N T Smentioning
confidence: 99%
“…Kuchler and his co-workers have put forward an interesting theory on the mechanism whereby the corticosteroids achieve their effects (158,159). The writers postulate, on the evidence obtained from experiments with synthetic steroids, such as estradiol and stilbestrol, that the drug molecules form a monolayer on the surface of the cell, thus preventing by occlusion of active sites, the transfer of ionized or highly polar substances across the cell membrane, as for example, amino acids.…”
Section: Methods Used I N Assessing the Beneficial A N D Adverse Effementioning
confidence: 99%